FORMULASI DAN UJI EFEKTIVITAS SEDIAAN KRIM BODY LOTION YANG MENGANDUNG EKSTRAK ETANOL AMPAS KOPI (Coffea arabica L.) - Pintata Sembiring (Program Studi Pendidikan Biologi, 2025)
Background: The phenomenon of beauty as part of a woman's lifestyle, its existence has been felt since centuries ago. Body lotion is a cosmetic preparation in the form of a liquid emulsion that is used on the hands and body with the aim of moisturizing and softening the skin. Coffee grounds are a by-product of coffee processing. Coffee grounds contain a number of fatty acids, amino acids, polyphenols, minerals, polysaccharides and flavonoid compounds that function as a source of natural antioxidants. Purpose: to formulate and evaluate body lotion preparations of Coffea arabica L extract and to determine its effectiveness on dry skin. Methods: coffee grounds were extracted by maceration using 96% ethanol as solvent and concentrated with a rotary evaporator. Arabica L coffee extract was formulated with concentrations of 5%, 10%, and 15% using a body lotion base consisting of stearic acid, triethanolamine, mineral oil and aquadest. Evaluation of the quality of the preparations included homogeneity, viscosity, stability and pH during 4 weeks of storage. Examination of moisture content, number of pores and blemishes on the skin of volunteers was carried out every week for 4 weeks. Results: All body lotion preparations were homogeneous, stable during storage for 4 weeks, viscosity 3105-5180 cp, pH 6.9-7.3, and not irritating. Increased skin moisture, decreased pores and blemishes using a body lotion preparation with a concentration of 15% was the same as the positive control. All body lotion preparations with Coffea arabica L extract can increase skin moisture. Conclusion: The most effective body lotion formula that is treat dry skin namely the preparation with 15% Coffea arabica L concentration and not significantly different from the positive control